2018
DOI: 10.1186/s12882-018-1068-1
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric continuous renal replacement therapy: have practice changes changed outcomes? A large single-center ten-year retrospective evaluation

Abstract: BackgroundTo evaluate changes in population characteristics and outcomes in a large single-center pediatric patient cohort treated with continuous renal replacement therapy (CRRT) over a 10 year course, coincident with multiple institutional practice changes in CRRT delivery.MethodsA retrospective cohort study with comparative analysis of all patients treated from 2004 to 2013 with CRRT in the neonatal, pediatric, and cardiovascular intensive care units within a free-standing pediatric tertiary care hospital.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 55 publications
1
26
0
1
Order By: Relevance
“…This study also showed the dramatic increase in morbidity and mortality in patients who required CRRT which has been previously reported [7,14,15]. As expected by PRISM-III scores, the overall mortality and morbidity rates in this study were high overall, but CRRT patients had signi icant morbidity burden and mortality rates as compared to patients who did not require CRRT.…”
Section: Discussionsupporting
confidence: 85%
“…This study also showed the dramatic increase in morbidity and mortality in patients who required CRRT which has been previously reported [7,14,15]. As expected by PRISM-III scores, the overall mortality and morbidity rates in this study were high overall, but CRRT patients had signi icant morbidity burden and mortality rates as compared to patients who did not require CRRT.…”
Section: Discussionsupporting
confidence: 85%
“…In a large multicenter observational study, only 1.5% of critically ill children underwent CRRT (2). A knowledge gap exists regarding clinical and technical peculiarities of CRRT in the pediatric population (7), and several researchers in the field encourage the sharing of experiences and clinical and technical data (8)(9)(10)(11). Predictors for circuit clotting are mostly unknown and originate from large cohorts of adult patients (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainties also exist on long-term kidney and global outcomes of critically ill pediatric patients who underwent CRRT. Although CRRT has been recognized as a strong predictor of short-term mortality, particularly when associated with fluid overload (FO) and MODS (14)(15)(16)(17), pediatric AKI patients undergoing CRRT often encounter delays in referral to the nephrology unit or are lost to long-term follow-up (10,18).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in our cohort, there was a significant protective effect from having pre-existing kidney disease against developing moderate to severe disability at discharge. We did not compare the severity of illness for the eleven survivors with pre-existing renal disease to the remainder of the cohort, but good global outcomes have been demonstrated in children receiving CKRT primarily for a renal indication in other cohorts [ 15 , 16 ]. Although not examined separately, there were more patients who received intermittent HD after CKRT in the worse FSS group compared to intact survival; whether this reflects the adverse impact of delayed kidney recovery on functional outcomes remains speculative and should be further investigated.…”
Section: Discussionmentioning
confidence: 99%